Effect of frequency and reaction time in focused ultrasonic pretreatment of energy cane bagasse for bioethanol production. (January 2016) - Methrath Liyakathali, Niyaz Ahamed; Muley, Pranjali D.; Aita, Giovanna; Boldor, Dorin
Highlights: Biomass pretreatment using ultrasonic generator with clamp-on ultrasonic transducer. Combination samples: energy cane, 28% NH4 OH and water in 1:0.5:8 (w:w:w) ratio. Ultrasonic frequencies (20, 20.5, 21 kHz) had no effect on enzymatic digestibility. Increase in reaction time and temperature enhanced enzymatic digestibility. Obtained maximum theoretical glucose yield of 24.29 g/100 g of dry energy cane. Abstract: Pretreatment of lignocellulosic biomass is a critical steps in bioethanol production. Ultrasonic pretreatment significantly improves cellulose hydrolysis increasing sugar yields, but current system designs have limitations related to efficiency and scalability. This study evaluates the ultrasonic pretreatment of energy cane bagasse in a novel scalable configuration and by maximizing coupling of ultrasound energy to the material via active modulation of frequency. Pretreatment was conducted in 28% ammonia water mixture at a sample:ammonia:water ratio of 1:0.5:8. Process performance was investigated as a function of frequency (20, 20.5, 21 kHz), reaction time (30, 45, 60 min), temperature, and power levels for multiple combinations of ammonia, water and sample mixture. Results indicated an increased enzymatic digestibility, with maximum glucose yield of 24.29 g/100 g dry biomass. Theoretical ethanol yields obtained ranged from 6.47 to a maximum of 24.29 g/100 g dry biomass. Maximum energy attainable was 886.34 kJ/100 g dry biomass.